2016
DOI: 10.1016/j.future.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

A web-based cooperative tool for risk management with adaptive security

Abstract: Risk management can benefit from Web-based tools fostering actions for treating risks in an environment, while having several individuals collaborating to face the endeavors related to risks. During the intervention, the security rules in place to preserve resources from unauthorized access, might need to be modified on the fly, e.g., increasing the privileges of risk managers or letting rescue teams view the exact position of the victims. Modifications should respect the overall security policies and avoid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…This section presents a general overview of risk management approaches against cyber-attacks. This study identified 23 primary studies, of which two focused on mobile [153,154], six focused on IoT devices [107,[155][156][157][158]181], two focused on cyber-physical systems [168,169], four focused on either fog computing [111,160], the 5G edge-cloud ecosystem [167], or connected and autonomous vehicle (CAV) [159], and eight in general [61,93,[161][162][163][164][165][166]. Furthermore, four primary studies focused on APT [93,107,111,160], while the others are focused on either specific attacks such as DDOS attacks [181], DOS [167], SQL injections attacks [181], or privilege-induced attacks [154], or non-specific attacks [60,61,140,[155][156][157][158][159][161][162][163][164][165][166]…”
Section: Rq2: What Are the Proposed Defensive Mechanisms Available To...mentioning
confidence: 99%
See 2 more Smart Citations
“…This section presents a general overview of risk management approaches against cyber-attacks. This study identified 23 primary studies, of which two focused on mobile [153,154], six focused on IoT devices [107,[155][156][157][158]181], two focused on cyber-physical systems [168,169], four focused on either fog computing [111,160], the 5G edge-cloud ecosystem [167], or connected and autonomous vehicle (CAV) [159], and eight in general [61,93,[161][162][163][164][165][166]. Furthermore, four primary studies focused on APT [93,107,111,160], while the others are focused on either specific attacks such as DDOS attacks [181], DOS [167], SQL injections attacks [181], or privilege-induced attacks [154], or non-specific attacks [60,61,140,[155][156][157][158][159][161][162][163][164][165][166]…”
Section: Rq2: What Are the Proposed Defensive Mechanisms Available To...mentioning
confidence: 99%
“…As shown in Figure 9, the existing studies either proposed risk management approaches [93,[154][155][156]158,159,161,[165][166][167][168][169] or were integrated with other approaches such as access control [161,164], situational awareness [61], and game theory [107,111,160,162].…”
Section: Rq2: What Are the Proposed Defensive Mechanisms Available To...mentioning
confidence: 99%
See 1 more Smart Citation
“…The paper ''A web-based cooperative tool for risk management with adaptive security'', by M. Fugini, and M. Teimourikia [8], based also on an initial contribution of G. Hadjichristofi, is in the area of cybersecurity and specifies a dynamic access control model for risks occurring in environments where persons, data objects and physical resources are represented both from the risk and from the cybersecurity perspective. Environmental risk management embraces various themes, from technologies of surveillance to strategies of risk treatment and security and privacy of the involved resources.…”
Section: Details About This Issuementioning
confidence: 99%
“…The synergy of CCCC supports the increasingly demanding performance specifications of these applications and helps to face special situations like unexpected condition adaptations, human interaction challenges, and goal conflicts. Practical industrial applications of the synergy of CCCC are cyber-physical systems [1][2][3][4][5], networked control systems [6][7][8][9][10], mechatronics systems [11][12][13][14][15], online quality control of production items [16][17][18][19][20], supervision and failure analysis of dynamically changing machine states [21][22][23][24], decision support systems [25][26][27][28][29], prediction and control in dynamic production processes [30][31][32], welding processes [33,34], user profiling [35,36], process monitoring [37][38][39], web based control of information management flows [40,41], and resilient control architectures [42][43][44]…”
mentioning
confidence: 99%